2010
DOI: 10.1590/s0103-51502010000100011
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do isostretching na resistência muscular de abdominais, glúteo máximo e extensores de tronco, incapacidade e dor em pacientes com lombalgia

Abstract: ResumoObjetivou-se determinar a influência do método Isostretching na resistência muscular do glúteo máximo, abdominais e extensores de tronco, incapacidade e dor de pacientes com lombalgia. Material e métodos: Este estudo caracterizou-se como um ensaio clínico aleatório, constituído de 18 mulheres, entre 18 e 25 anos, com dor cinco ou mais na escala visual análoga (EVA) na região lombar, no mínimo três vezes por semana, randomizadas em grupo ativo e controle. Foram excluídas as submetidas a tratamentos fisiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 19 publications
(14 reference statements)
2
20
0
12
Order By: Relevance
“…These results agree with those of Macedo et al (26), who administered 20 isostretching sessions with nine female patients with low back pain, given that both showed a statistically signi icant improvement in the strength of trunk extensors. These results also agree with indings of Rosary et al (29), which showed improved muscle strength in ten women with eight RPG sessions, where postures were administered in the coxo-femoral angle opening and closure.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results agree with those of Macedo et al (26), who administered 20 isostretching sessions with nine female patients with low back pain, given that both showed a statistically signi icant improvement in the strength of trunk extensors. These results also agree with indings of Rosary et al (29), which showed improved muscle strength in ten women with eight RPG sessions, where postures were administered in the coxo-femoral angle opening and closure.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the present study, in addition to these mentioned indings, Macedo et al (26) also found a statistically signi icant difference in improved abdominal strength, trunk and gluteal extension when compared to the control group. Strength gain favors stability of the spine joints, which will support the resolution of the condition and prevention of relapses.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations